Design and Development of a Web-Based Booking and Employee Management System Using Agile Methodology - Kesya Sakha Nesya Arimawan; Reisa Permatasari; Seftin Fitri Ana Wati (Universitas Islam Kuantan Singingi, 2026)
The rapid advancement of information technology has compelled business sectors to undergo digital transformation to enhance competitiveness. April Photo Studio previously relied on manual methods for booking and employee management, resulting in issues such as unrecorded orders, slow response times, and inaccurate scheduling. To address these problems, this study adopted the Agile development methodology to design and build a web-based information system. This methodological approach facilitated an iterative development lifecycle consisting of planning, implementation, testing, and maintenance phases while utilizing the Laravel framework and Model View Controller architecture. The resulting system integrates online booking, digital payments, and shift management features. Results indicate that the system successfully streamlined the booking process, improved data accuracy, and increased transparency in employee management. In conclusion, the implementation of this system enhanced operational effectiveness and established a structured workflow at April Photo Studio.